Physical Activity and Breast Cancer Prevention: Possible Role of Immune Mediators - Xu, Yitong; Rogers, Connie J. (Frontiers in Nutrition, 2020)
.There is strong evidence that physical activity (PA) reduces risk, recurrence and mortality from breast cancer. Emerging data suggest that PA induces changes in inflammatory and immune mediators that may contribute to beneficial effects on breast cancer outcomes. A literature search was conducted to identify studies that evaluated the impact of PA on tumor and immune outcomes in breast cancer patients and in mammary tumor models. Nineteen studies investigated the effect of PA interventions on cancer immune outcomes using preclinical breast cancer models. Tumor growth was reduced in 11 studies, unchanged in three studies, and increased in one study. Spontaneous metastasis was reduced in two studies and survival was improved in four studies. Frequently assessed immune outcomes include splenic cell number and function, circulating inflammatory cytokines, and intratumoral immune cells and inflammatory markers. Circulating inflammatory cytokine responses were heterogeneous in preclinical models. Within the tumor microenvironment (TME), several studies documented a change in the infiltration of immune cells with an increase in effector cells and a reduction in immune suppressive cells. Twenty-three studies investigated the effect of PA interventions on immune outcomes in breast cancer patients. Thirteen studies used aerobic PA interventions and ten studies used a combination of aerobic and resistance exercise interventions. Cycling and treadmill activities were the most commonly used PA modalities. Circulating immune cells and inflammatory cytokines were the most frequently assessed immune outcomes in the clinical studies. Among the 19 studies that evaluated a PA intervention during the post treatment period, 10 reported a reduction in the levels of at least one inflammatory cytokine. No inflammatory cytokines were quantified in the three studies that evaluated a PA intervention during treatment with chemotherapy. Immune outcomes within the tumor were assessed in only one study performing a PA intervention prior to surgery. Results from preclinical and clinical studies suggest that PA exerts heterogeneous effects on inflammatory cytokines, but may alter the gene expression profile and immune infiltrates in the tumor which may result in a reduction in immunosuppressive factors. However, additional studies are needed to better understand the effect of PA on immune outcomes in the TME.